Aktivitas Antibakteri Daun Kemangi (Ekstrak, Fraksi Kloroform, dan Fraksi n-Heksan) terhadap Staphylococcus aureus dan Eschericia coli - Melati Yulia Kusumastuti; Debi Meilani; Suhendra Tawarnate (LPPM STIKes Indah Medan, 2021)
Basil (Ocimum citriodorum Vis.) is a plant which is their leaves are commonly eaten as fresh vegetables and has many benefits. Basil leaves contains secondary metabolite compounds that have antibacterial activity such as flavonoids, tannins, saponins, alkaloids, and steroids. The purpose of this study was to known the antibacterial activity of some fractions of basil leaves against Escherichia coli and Staphylococcus aureus and see which fraction was more active.This research included extraction by maceration method using ethanol 96%, then ethanol extract was fractionated using n-hexane and chloroform, phytochemical screening, then tested for antibacterial activity against E. coli and S. aureus by using agar diffusion method. Phytochemical screening showed ethanol extract contained alkaloids, saponins, flavonoids, tannins and steroids; chloroform fraction contained alkaloids, flavonoids, saponins, and tannins; and n-hexane fraction contained steroids. The results of the antibacterial activity test showed ethanol extract and chloroform fraction had antibacterial activity. Meanwhile, n-hexane fraction did not have antibacterial activity. Concentration of 500 mg / ml of chloroform fraction and ethanol extract on S. aureus resulted inhibition zone around 24.67-26.90 mm. Furthermore, on E. coli produced 22.67-23.84 mm. Ethanol extract had higher antibacterial activity than the chloroform fraction against E. coli and S. aureus.